Normative Study Of The Influence Of Social Media Social Media Influence On Prostitution Crime Based On Social Control Theory Social Control Theory - Hurairah, Hurairah; Royani, Ferawati (Fakultas Hukum Dehasen, 2025)
Crime is a social problem that is not only faced by Indonesia or certain communities and countries, but is a problem faced by the entire world community. Social media is media in the form of sites and applications involving internet-based technology. Social media is an online media through internet-based applications, can be used to share, participate and create content in the form of blogs, wikis, forums, social networks and virtual world spaces supported by increasingly sophisticated and powerful multimedia technology. The legal research method used is normative, normative legal research (legal research). Prostitution is known by society as a form of social disease that occurs in some circles. Social media has two impacts, namely positive and negative, but as technology develops, it is misused as a tool to facilitate the disease of the masses, namely prostitution, both carried out by women and men. this crime does not look at gender, all have the potential to commit criminal acts of prostitution, this can be done in theory, namely social control theory, with social control can be done internally and externally, as well as preventive and repressive efforts.